Evaluation of a Positive Youth Development Program Based on the Repertory Grid Test - Daniel T. L. Shek (The Scientific World Journal)
The repertory grid test, based on personal construct psychology, was used to evaluate the effectiveness of Project P.A.T.H.S. (Positive Adolescent Training through Holistic Social Programmes) in Hong Kong. One hundred and four program participants (n=104) were randomly invited to complete a repertory grid based on personal construct theory in order to provide both quantitative and qualitative data for measuring self-identity changes after joining the program. Findings generally showed that the participants perceived that they understood themselves better and had stronger resilience after joining the program. Participants also saw themselves as closer to their ideal selves and other positive role figures (but farther away from a loser) after joining the program. This study provides additional support for the effectiveness of the Tier 1 Program of Project P.A.T.H.S. in the Chinese context. This study also shows that the repertory grid test is a useful evaluation method to measure self-identity changes in participants in positive youth development programs.